Development of Airport-Related Zones (The Construction of The Airport City) as An Element of The Interdependent Development of Airports, Agglomerations and Regions â GdaÅsk Airport Case Study - MaÅgorzata Wach-Kloskowska (The Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
This paper presents the most important issues and premises for the targeted development of airport-related areas, with particular emphasis on the planned implementation of a so-called airport city in the immediate vicinity of an airport. The investigation sought to answer questions about how airports perform city- and region-forming functions, to systematize the existing concepts of the implementation of airport cities based on the relevant literature, and to present the principles of proper design of airport-related zones. Key premises for the development of airport cities and benefits for their users are also discussed. Detailed considerations about GdaÅ„sk Airport provide an example of the application of a qualitative method in an individual case, confirmed by observation and in-depth interviews. The adopted structure of the study and the research methodology were based mainly on literature studies and a critical review of the literature as well as on face-to-face interviews, on-site observation and analysis of feedback between the airport and the spatial development of the airport zone. The conclusion indicates development directions for airport zones depending on the location, characteristics and potential development of the airport itself and the region it is located in.The case study of GdaÅ„sk Airport and the development of its airport-related zone show a clear trend in the application of the airport city model implemented at other airports in the world, taking into account good practices and the principles of the proper design of existing airport cities/aerotropolises.Abstrak. Makalah ini menyajikan isu-isu dan lokasi yang paling penting untuk pengembangan yang ditargetkan di sekitar bandara dengan penekanan khusus pada implementasi dari apa yang direncanakan sebagai kota bandara. Studi ini menjawab pertanyaan-pertanyaan tentang bagaimana bandara berfungsi sebagai pembentuk perkembangan kota dan wilayah, sistematisasi konsep implementasi kota bandara berdasarkan literatur yang relevan, dan menyajikan prinsip-prinsip desain yang tepat pada zona-zona yang terkait bandara. Makalah ini juga membahas tempat-tempat utama untuk pengembangan kota bandara dan manfaat bagi penggunanya. Pertimbangan terperinci tentang Bandara GdaÅ„sk sebagai kasus adalah contoh penerapan metode kualitatif, yang dikonfirmasi melalui observasi dan wawancara mendalam. Struktur penelitian yang diadopsi dan metodologi penelitian didasarkan terutama pada studi literatur dan tinjauan kritisnya, wawancara tatap muka, observasi lokasi dan analisis umpan balik antara bandara dan pengembangan spasial zona bandara. Kesimpulan menunjukkan arah pengembangan untuk zona bandara tergantung pada lokasi, karakteristik dan potensi pengembangan bandara itu sendiri dan di wilayah mana bandara tersebut berada. Studi kasus Bandara GdaÅ„sk dan pengembangan zona terkait bandara menunjukkan tren yang jelas dalam penerapan model kota bandara yang diterapkan di bandara-bandara lain di dunia, dengan mempertimbangkan praktik-praktik yang baik dan prinsip-prinsip desain yang tepat saat ini dari kota bandara/aerotropolis..Kata kunci: kota bandara, pengembangan spasial, infrastruktur transportasi, area terkait bandara, pengembangan regional.